2021
DOI: 10.1057/s41272-021-00290-6
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal balancing of revenue and demand in hotel industry: the case of Dubai City

Abstract: For fact, a strong demand seasonality is observed in hotel industry, which needs early planning to prevent revenue declines. Cost cuts, although sometimes deemed tolerable, no longer help because expenditures have thresholds that hardly can be crossed. Increasing the revenue by raising rates, on the other side, adversely affects the level of demand. In low seasons, travelers are more sensitive to prices, and therefore, higher rates turn customers away to other rivals. To address the compromise between demand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Deboosere et al (2019) and Casamatta et al (2022) found that hosts adjust their prices based on the holiday calendar and seasonal demand. Alrawabdeh (2022) highlights that different international and local hotels may exhibit varying price fluctuations throughout the year. We find there is a difference between professional and opportunistic owners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deboosere et al (2019) and Casamatta et al (2022) found that hosts adjust their prices based on the holiday calendar and seasonal demand. Alrawabdeh (2022) highlights that different international and local hotels may exhibit varying price fluctuations throughout the year. We find there is a difference between professional and opportunistic owners.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality plays a pivotal role in shaping pricing dynamics and performance disparities among STRs, as noted by various researchers. Several authors (Aznar et al, 2018;Magno et al, 2018;Falk et al, 2019;Sainaghi et al, 2021;Casamatta et al, 2022;Yilmaz et al, 2022;Alrawabdeh, 2022) consider seasonality one of the most important factors explaining price and performance differentials among Airbnb properties. They find that during the summer or peak season, for example, when school starts, a higher degree of market power is more probable, impacting pricing and performance within the Airbnb market.…”
Section: Monthly Pricing By Season For Str Apartmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonality and its effects are investigated in the article by developing elasticity model to benchmark airlines strategic performance. On the other hand, Alrawabdeh ( 2021 ) argues that variability is a recurring phenomenon, and therefore, seasonality in customer demand should be studied and forecasted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has always been a case that seasonality is an inherent issue in the hotel industry. Alrawabdeh ( 2021 ) proposes a model that tests the balance of seasonal demands and prices to maximize hoteliers’ profit. Specifically, the authors present an approach that finds the seasonal elasticity of demand at the optimum profit.…”
mentioning
confidence: 99%